2013
DOI: 10.4161/cc.24879
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to light at night accelerates aging and spontaneous uterine carcinogenesis in female 129/Sv mice

Abstract: The effect of the constant illumination on the development of spontaneous tumors in female 129/Sv mice was investigated. Forty-six female 129/Sv mice starting from the age of 2 mo were kept under standard light/dark regimen [12 h light (70 lx):12 hr dark; LD, control group], and 46 of 129/Sv mice were kept under constant illumination (24 h a day, 2,500 lx, LL) from the age of 5 mo until to natural death. The exposure to the LL regimen significantly accelerated body weight gain, increased body temperature as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 35 publications
(46 reference statements)
1
6
0
Order By: Relevance
“…In EPT-treated mice, progesterone did not increase mammary cancer risk (Figure 1D), but its dose was insufficient to inhibit uterine stimulation during the luteal phase of the estrous cycle (Figure 7B). However, in MEPT mice, melatonin supplementation significantly decreased mammary cancer risk without overstimulating the uterus to further support the previous reports of melatonin's uterine protective effects (53, 93, 139). Therefore, combining melatonin with a progesterone-containing HT resulted in reduced uterine stimulation in addition to mammary cancer protection.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In EPT-treated mice, progesterone did not increase mammary cancer risk (Figure 1D), but its dose was insufficient to inhibit uterine stimulation during the luteal phase of the estrous cycle (Figure 7B). However, in MEPT mice, melatonin supplementation significantly decreased mammary cancer risk without overstimulating the uterus to further support the previous reports of melatonin's uterine protective effects (53, 93, 139). Therefore, combining melatonin with a progesterone-containing HT resulted in reduced uterine stimulation in addition to mammary cancer protection.…”
Section: Discussionsupporting
confidence: 87%
“…Melatonin binding analyses indicate that the uteri remain melatonin-sensitive through age 14 months (Figure 8A). Previous studies report that melatonin inhibits estrogen stimulation of the uterus since LAN accelerates spontaneous uterine carcinogenesis in mice (139) and co-administration of melatonin and estradiol in ovariectomized rats decreases endometrial thickness and prevents atypia compared to the estrogen-only group (93). In women, a higher risk of endometrial cancer is also associated with lower levels of melatonin and night shift work (53).…”
Section: Discussionmentioning
confidence: 99%
“…Body weight gain was reduced after prolonged exposure of female rats to CL conditions, consistent with results of Vinogradova et al (). However, some authors reported no change (Baldissera et al, ) or even increase in body weight gain (Fonken et al, ; Popovich et al, ; Coomans et al, ). This discrepancy may be due to differences between the studies, namely the duration of exposure to CL treatment, intensity of illumination, and/or different rats' age at the beginning of the treatment.…”
Section: Discussionmentioning
confidence: 99%
“…By phenotyping transgenic mice with mutant and/or deleted clock genes, a direct link was made between the circadian clock and the metabolic disorders. Moreover, disrupting the circadian system -either by repetitive jet lag [45] or by light exposure at night [46,47] -has been shown to increase mortality in ageing mice.…”
Section: Disruption Of the Light-dark Cycle And The Effect On Metabolismmentioning
confidence: 99%